2019
DOI: 10.1111/jfpp.14349
|View full text |Cite
|
Sign up to set email alerts
|

A new rye‐based beverage with high polyphenols and amino acids: Production and study of physicochemical and sensory properties

Abstract: The healthy and nutritionally rich drinks are increasingly demanded in many countries. The rye extract‐based drink was produced and sweetened with either saccharose (B) or apple concentrate (C) and was compared with malt‐based (A), nonalcoholic drink. Based on sensorial evaluations, drink with 5% rye extract concentrate was selected with a pleasant acidic and a unique flavor. The higher phenolic content (A: 5.3 ± 0.11, B: 16.6 ± 1.09, and C: 14.1 ± 0.35 mg GAE/ml), remarkable amino acids concentration, the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…24 However, the ability of yeast to accumulate phenolic compounds has been reported. 25,26 A decrease in phenolic compounds up to 50% in faba bean during 6-day tempe fermentation was also observed by Polanowska et al 27 Nevertheless, kvasses prepared in this study were characterized by a higher TPC value at least by 21% per 1 mL than fermented beverages based on rye extract prepared by Rokhsartalab-Azar et al 28 The results regarding chromatographic analysis of phenolic compounds confirmed the aforementioned observations (Table 2). It can be seen that during fermentation the stability of phenolic compounds introduced to the sample with RME was less 23 Also, quercetin and myricetin derivative contents were the highest in sample R1 and fermentation did not cause significant changes in their amounts.…”
Section: Tpc Phenolic Compounds and Abtssupporting
confidence: 87%
“…24 However, the ability of yeast to accumulate phenolic compounds has been reported. 25,26 A decrease in phenolic compounds up to 50% in faba bean during 6-day tempe fermentation was also observed by Polanowska et al 27 Nevertheless, kvasses prepared in this study were characterized by a higher TPC value at least by 21% per 1 mL than fermented beverages based on rye extract prepared by Rokhsartalab-Azar et al 28 The results regarding chromatographic analysis of phenolic compounds confirmed the aforementioned observations (Table 2). It can be seen that during fermentation the stability of phenolic compounds introduced to the sample with RME was less 23 Also, quercetin and myricetin derivative contents were the highest in sample R1 and fermentation did not cause significant changes in their amounts.…”
Section: Tpc Phenolic Compounds and Abtssupporting
confidence: 87%
“…Thus, natural preservatives from sources like plants were reported to ensure food safety due to their antibacterial activity (Fourati et al., 2020; Ben Hlima et al., 2019; Smaoui et al., 2019). One of the readily available sources of such compounds is by‐products from the agro‐food industry which proposed a rich source of active compounds and had a potential in health benefits (Albertos, Rico, & Martin‐Diana, 2020; Khaled, Dahmoune, Madani, Urieta, & Mainar, 2020; Muangrat & Jirarattanarangsri, 2020; Rokhsartalab‐Azar, Jafari, Tukmechi, & Malekinejad, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the readily available sources of such compounds is by-products from the agro-food industry which proposed a rich source of active compounds and had a potential in health benefits (Albertos, Rico, & Martin-Diana, 2020;Khaled, Dahmoune, Madani, Urieta, & Mainar, 2020;Muangrat & Jirarattanarangsri, 2020;Rokhsartalab-Azar, Jafari, Tukmechi, & Malekinejad, 2020).…”
mentioning
confidence: 99%